Antepartum haemorrhage: a retrospective analysis in a tertiary care centre - Rajoriya, Mohini; Dubey, Saurabh; Agarwal, Sanju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Aim of the present study was to found the incidence of APH, demographic profile risk factors and maternal outcome. Methods: This was a retrospective study carried out in Department of Obstetrics and Gynaecology, MGM Medical College and associated M.Y., Hospital, Indore from August 2019 to July 2020. Results: The incidence of APH was 3.27%. 68.7% cases of APH were associated with pregnancy induced hypertension suggesting PIH is one of the major risk factors. Maternal morbidity was very high with increased rates cesarean section 91.7%, postpartum hemorrhage (32.6%), need of blood transfusion (86%). There were 2 mortalities and 3.1 % patients underwent Obstetric Hystrectomy and 24% required CCU admission. Conclusions: There is very high maternal morbidity and mortality in APH.